The Validation of LIAA (Linguistic Intelligence Assessment Android) Development In Elementary School - Kurniaman, Otang; Hidayat, Muhammad Luthfi; Noviana, Eddy; Munjiatun, Munjiatun; Kurniawan, Kurniawan (Profesi Pendidikan Dasar, 2020)
This study provides an overview of the validation results of teachers and media experts to assess the LIAA (Linguistic Intelligence Assessment Android) application, using the research and development method. This method is used to develop a product and tests its effectiveness. However, this article is just for developing and designing LIAA. The results of the study showed response proportion: Â 78% for the teacher's language use, 84% for ease of application,Â  75% for final clarity of assessment, 84% for the presentation, 72% for the average of the final assessment test. Validation from media experts to assess the appropriateness of using the LIAA application with an average of 88% (very valid category). So it is concluded that the LIAA application can be applied on a wide scale in measuring the linguistic intelligence of elementary school students.